2010
DOI: 10.1038/nature09374
|View full text |Cite
|
Sign up to set email alerts
|

HAATI survivors replace canonical telomeres with blocks of generic heterochromatin

Abstract: The notion that telomeres are essential for chromosome linearity stems from the existence of two chief dangers: inappropriate DNA damage response (DDR) reactions that mistake natural chromosome ends for double-strand DNA breaks (DSBs), and the progressive loss of DNA from chromosomal termini due to the end replication problem. Telomeres avert the former peril by binding sequence-specific end-protection factors that control the access of DDR activities. The latter threat is tackled by recruiting telomerase, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 36 publications
4
81
0
Order By: Relevance
“…In S. pombe, the catalytic subunit of telomerase is encoded by the trt1 ϩ gene. The deletion of trt1 ϩ produces circular survivors or survivors that maintain telomeres by HR (65,66). We found that the trt1⌬ rqh1⌬ double mutant is not lethal, but the telomeres of the double mutant are maintained by HR, and we could not obtain a double mutant with circular chromosomes (23).…”
Section: Discussionmentioning
confidence: 75%
“…In S. pombe, the catalytic subunit of telomerase is encoded by the trt1 ϩ gene. The deletion of trt1 ϩ produces circular survivors or survivors that maintain telomeres by HR (65,66). We found that the trt1⌬ rqh1⌬ double mutant is not lethal, but the telomeres of the double mutant are maintained by HR, and we could not obtain a double mutant with circular chromosomes (23).…”
Section: Discussionmentioning
confidence: 75%
“…The trt1 single mutant was not sensitive to TBZ when cells were grown in liquid culture both in early generations that have telomeric DNA and in late generations that have linear chromosomes in a recombination-dependent manner, demonstrating that the telomere recombination itself is not the cause of the TBZ sensitivity (M. Ueno, unpublished observations). However, a third type of trt1 survivor called HAATI has been reported (18). This survivor shares some phenotypes with the pot1⌬ rqh1-hd double mutant, including HR-dependent maintenance of the chromosome ends and stacking chromosomes at wells of the pulsed-field gel.…”
mentioning
confidence: 99%
“…They do not have telomeric DNA at the chromosome ends and need Pot1 to maintain the chromosome ends, further supporting the possibility that Pot1 protects chromosome ends regardless of the sequence of the ends. 4) The reason for the synthetic lethality of the pot1Á rqh1Á double mutant might be a defect in the SSA. Indeed, S. cerevisiae Sgs1 is required for efficient A and B, The telomere lengths of the wild-type, trt1Á, rqh1-hd, and trt1Á rqh1-hd cells (A) and trt1Á rqh1-hd rad51Á cells (B) were measured by Southern hybridization at 30 C. Genomic DNA was digested with EcoRI, separated by 1.0% agarose gel electrophoresis, and hybridized to a 1-kbp DNA fragment containing telomere plus TAS1 sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a third type of survivors was reported, in which chromosome ends have non-telomeric heterochromatin. 4) Unlike the trt1Á disruptant, deletion of pot1 þ (which encodes the singlestranded telomere binding protein) causes rapid telomere loss, and only one type of survivor, in which chromosomes are circularized, arises. 5) This chromosome circularization is mediated by single-strand annealing (SSA).…”
mentioning
confidence: 99%